The floral transcriptome of Machilus yunnanensis, a tree in the magnoliid family Lauraceae. (December 2018) - Song, Yu; Gan, Yi; Liu, Liangyu; Corlett, Richard T.
Highlights: Machilus yunnanensis Lecomte is an important Chinese timber species in the family Lauraceae, subclass Magnoliidae. Here, RNA-seq for transcriptome analysis showed that similar gene expression patterns in the temperature, gibberellin, brassinosteroid, and auxin mediated flowering pathways between M. yunnanensis and Arabidopsis . Our study provides a clear gene network for flowering and related plant hormone regulating crosstalk in M. yunnanensis, and shows that the temporal regulatory programs in the development of flower organs of Machilus are similar to those in the very different flowers of Arabidopsis . Abstract: Machilus yunnanensis Lecomte is an important Chinese timber species in the family Lauraceae, subclass Magnoliidae. To understand the genetic and molecular basis of flowering in M. yunnanensis, we applied RNA-seq for transcriptome analysis of young and mature flowers and compared these with the transcriptome of leaves. From approximately 26 Gb Illumina clean reads, we obtained a total of 85 823 high-quality transcripts using Trinity software. Comparisons of gene expression in young and mature flowers showed that 37 877 genes were differentially expressed. Among those genes, 121 and 111 genes are implicated in the flowering network and in plant hormone signaling transduction, respectively. Moreover, 141 homologs of these genes displayed similar expression patterns during flower development in M. yunnanensis and Arabidopsis thaliana . Using cluster analysis, we further compared the gene expression profiles in the different pathways that control flowering and phytohormone signaling, and found similar gene expression patterns in the temperature, gibberellin, brassinosteroid, and auxin mediated flowering pathways. Our study provides a clear gene network for flowering and related plant hormone regulating crosstalk in M. yunnanensis and shows that the temporal regulatory programs in the development of flower organs of Machilus are similar to those in the very different flowers of Arabidopsis .